IMPLEMENTASI MEDIA AUGMENTED REALITY DALAM MENINGKATKAN MINAT BACA BAHASA INDONESIA SISWA KELAS IV UPT SDN 20 TURATEA KABUPATEN JENEPONTO - Muthmainnah, Sayyidatul; M. Agus; Aco Karumpa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is how the implementation of augmented reality media in increasing interest in reading Indonesian language of fourth grade students of UPT SDN 20 Turatea, Jeneponto Regency. This study aims to increase students'interest in reading through Augmented Reality media of fourth grade students of UPT SDN 20 Turatea, Jeneponto Regency. This type of research is classroom action research consisting of two cycles where each cycle is carried out for three meetings. The research procedure includes planning, implementation of actions, observation, and reflection. The subjects in this study were 24 fourth grade students of UPT SDN 20 Turatea, Jeneponto Regency. The results showed that in the first cycle that was completed individually from 24 students, only 5 or 19% met the Learning Objective Achievement Criteria (KKTP) or were in the low category. Classically it has not been met because the average value obtained was 60.4%. Meanwhile, in cycle II, 20 out of 24 students, or 83%, had fulfilled the KKTP (Eligible Card) and classically, the average score obtained was 79.1%, or in the high category. Based on the results of the study above, it can be concluded that learning Indonesian by fourth-grade students at UPT SDN 20 Turatea, Jeneponto Regency through Augmented Reality media has increased.